Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1101/508697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased signal diversity/complexity of spontaneous EEG, but not evoked EEG responses, in ketamine-induced psychedelic state in humans

Abstract: Objective : It is not well understood how and to what extent electrical brain activity is affected in pharmacologically altered states of consciousness, where the phenomenological content rather than the level is consciousness is mainly altered. An example is the moderately «psychedelic» state caused by low doses of ketamine. Therefore, we investigated whether and how measures of evoked and spontaneous electroencephalographic (EEG) signal diversity are altered by sub-anaesthetic levels of ketamine compared to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Co-author Bjørn E. Juel is presently also affiliated with The Department of Psychiatry, Center for Sleep and Consciousness, University of Wisconsin, Madison, WI, USA. Results from this work were previously presented at two conferences in 2017 [58,59] and as a preprint manuscript in January 2019 [60].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Co-author Bjørn E. Juel is presently also affiliated with The Department of Psychiatry, Center for Sleep and Consciousness, University of Wisconsin, Madison, WI, USA. Results from this work were previously presented at two conferences in 2017 [58,59] and as a preprint manuscript in January 2019 [60].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Finally, both ERP and signal diversity based measures have been shown to be influenced by processes that are unlikely to relate to the presence of consciousness per se. For example, some ERP based measures like the auditory evoked P300b response has been shown to disappear if the subject is paying attention to something else than the auditory stimulus (Bekinschtein et al, 2009) , and the signal diversity based measure LZc has been shown to be reduced when subjects close their eyes (Farnes et al, 2020) or increase during psychedelic experiences (Schartner, Carhart-Harris, et al, 2017) . In other words, certain non-rest cognitive or physiological conditions in which subjects are conscious could serve as a test against false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…However, newer results have shown that signal diversity might be regionally differentiated and that global measures may not be sufficiently specific (Schartner, Pigorini, et al, 2017) . For example, when measuring EEG with eyes closed, synchronous alpha-activity in occipital regions may lead to a drop in the global measures of signal diversity even without an overall change in state of consciousness (Farnes et al, 2020) .…”
Section: Signal Diversitymentioning
confidence: 99%
“…Several complexity measures have also been found to increase for ketamine-induced states compared to normal waking consciousness ( Schartner et al. 2017b ; Farnes et al. 2019 ).…”
Section: Resting-state Neural Complexity and Dimensions Of Consciousnessmentioning
confidence: 99%